Evaluasi Rasionalitas Penggunaan Obat Ditinjau dari Indikator Peresepan Menurut World Health Organization (WHO) di Seluruh Puskesmas Kota Kendari Tahun 2016 - Sunandar Ihsan; Sabarudin Sabarudin; Mesi Leorita; Andi Sitti Zaenab Syukriadi; Merlyn H. Ibrahim (Halu Oleo University, 2017)
ABSTRACTBackground: Puskesmas is a first level of health facility in the public health services and for that, rationality drug used is important to achieve a better quality of life supporting productivity and nationality endurance. Aim: This study aim to evaluated rationality of drug used thorough WHO prescribing indicator to all subdistrict public health (Puskesmas) in Kendari City. Method: This was a cross sectional observational study at 15 subdistrict public health service with restrospective data collected. Total sample was 1680 prescription for 2016 period. Data compare with WHO standard indicator. Result: Result of this study showed that average drug prescriber was 3.23, average percentace of medicine prescribed by generic name was 96.08%, average percentage encounters with antibiotic prescribed was 36.85%, average percentage encounters with injection prescribed was very low 0.16%, average percentage of medicine with National Formularium was 75.07%. Result showed that drug used at all Puskesmas was still irrational except injection used and there was significant difference (p<0.005) between Puskesmas except injection used. There were three Puskesmas (Puskesmas Labibia, Puskesmas Kemaraya, and Puskesmas Benu-benua) has achieved standard of percentage of drug prescribed. Antibiotic achieved standard used was Puskesmas Nambo, Puskesmas Benu-benua, Puskesmas Wua-wua, Puskesmas Labibia and Puskesmas Perumnas. There were no one Puskesmas has achieved generic names and national formularium prescribed.Conclusion: Puskesmas Benubenua was most rational drug use with prescribing indicator of WHO.Keywords: Rational Drug Use, Prescribing Indicator, Puskesmas, Kendari City